Two new species of mites in the family Pachylaelapidae from Türkiye (Acari: Mesostigmata) - Özbek, Hasan Hüseyi̇n; Halliday, Bruce (Zootaxa, 2024)
This study reviews some species of mites in the family Pachylaelapidae from Türkiye. Onchodellus marginatus sp. nov. and Pachylaelaps (Longipachylaelaps) vermiger sp. nov. are described as new species. Olopachys (Olopachys) caucasicus Koroleva, 1976, and Pachylaelaps (Pachylaelaps) imitans Berlese, 1920 are re-described on the basis of newly-collected specimens.